GAMBARAN KADAR SERUM INTERLEUKIN-6 PADA PEROKOK AKTIF - I Gusti Agung Dewi Sarihati; Kadek Ika Surya Cahyani; Ida Ayu Sri Arjani; Surya Bayu Kurniawan; Heri Setiyo Bekti (Meditory : The Journal of Medical Laboratory, 2020)
AbstractCigarette smoke contains Reactive Oxygen Species (ROS). ROS when it is over-produced causes  oxidative stress. Oxidative stress is related to the synthesis of pro-in-flamatory cytokines  which encourage inflammation which is characterized by the increase in proinflammatory cytokines. The purpose of this study was to determine the description of serum interleukin-6 levels in active smokers. The research sample was 11 active smokers in the Bali Regional Police who were selected using a non- probability sampling technique using purposive sampling. Measurement of serum interleukin-6 levels was performed using the ELISA method. The results showed that serum interleukin-6 levels increased in all age groups and most were found at the age of 35-44 years (36.3%), with normal and obese BMI each 45.5%, in white cigarette smokers with filters (72.7%), moderate smoking intensity (63.6%), with smoking duration of 11-15 years (36.4%). The conclusion in this study is that most active smokers have increased serum interleukin-6 levels. Keywords: active smokers, serum, interleukin-6